“Men First, Subjects Afterward”: Thoreau, “Civil Disobedience,” and the Thoreauvian Echoes of 1968 and After - Bakratcheva, Albena Kouzmanova (Review of International American Studies, 2019)
Thoreau's political reputation in the United States dates from the 1960s when the Americans began to see themselves in a political context. The single most famous fact of Thoreau's life had once been perceived as his going off to Walden Pond in order to drive life into a corner; in the sixties that was superseded by Thoreau's night spent in jail in order to drive the government into a corner. This paper will deal with Thoreau’s impact in both the US and Europe in 1968, as well as two decades later when ‘Civil Disobedience’ became the slogan of the velvet revolutions in Eastern Europe.